2019
DOI: 10.1177/1054773819883171
|View full text |Cite
|
Sign up to set email alerts
|

Music Interventions in Percutaneous Coronary Procedures: A Meta-Analysis

Abstract: To clarify the effectiveness of music intervention for improving the well-being of patients undergoing coronary procedures for coronary heart disease, we conducted full-text searches of various databases (MEDLINE, Cochrane Library, CINAHL, ProQuest, and Airiti Library; 1966–2019) to identify randomized controlled trials and quasi-experimental studies of music intervention in recipients of angiography or percutaneous coronary intervention. Outcome measures included anxiety, discomfort, pain, heart rate, and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…It was observed that musical intervention is effective in reducing anxiety, but it does not apply for the assessment of pain, HR and BP, whose results indicate that musical intervention was not superior to routine care. The meta-analysis concluded that studies included in the sample are heterogeneous and suggested performing new high-quality RCTs with music intervention to confirm these findings [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that musical intervention is effective in reducing anxiety, but it does not apply for the assessment of pain, HR and BP, whose results indicate that musical intervention was not superior to routine care. The meta-analysis concluded that studies included in the sample are heterogeneous and suggested performing new high-quality RCTs with music intervention to confirm these findings [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies have been used to treat anxiety in patients undergoing cardiac catheterization; among them, music interventions have received attention from researchers [ 1 , 2 , 3 ]. The therapeutic use of music is recognized for its low cost [ 4 ], ease of application, and good acceptability [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been used to treat anxiety in patients undergoing cardiac catheterization; among them, music interventions have received attention from researchers [ 1 , 2 , 3 ]. The therapeutic use of music is recognized for its low cost [ 4 ], ease of application, and good acceptability [ 1 , 2 , 3 , 4 ]. However, the results of studies on the effectiveness of these interventions are controversial [ 2 , 3 ], which can be attributed to little attention being paid to the mechanisms of action of music for achieving the desired health outcomes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations